MARINE POLLUTION IN LAMPUNG PROVINCE: THE STATE IS POWERLESS AGAINST ENVIRONMENTAL DESTROYERS: PENCEMARAN LAUT PROVINSI LAMPUNG: NEGARA TAK BERDAYA MELAWAN PERUSAK LINGKUNGAN - Musril, Irfan Tri (Constitutional Law Society, 2024)
Law enforcement efforts in order to provide a deterrent effect against perpetrators of environmental crimes and force the perpetrators to be responsible for the impacts caused by pollution or damage that occurs based on the polluter pays principle as contained in Law 32/2009. pollution and / or oil spills in Lampung sea waters continue to occur throughout 2020 - 2022. This study aims to determine how the legal liability of PT Pertamina due to PHE OSES pipe leakage on the east coast of Lampung with an empirical juridical approach using primary and secondary data sources. the conclusion of this study is: The State is still hesitant in applying criminal law against perpetrators of marine pollution due to oil spills; in cases of marine pollution due to oil spills, the state prefers to apply administrative sanctions and / or civil law enforcement. In the case of the implementation of civil sanctions, there is a weakness of the government in supervising the implementation of sanctions so that the perpetrators of pollution have a low level of compliance in the implementation of sanctions.